Why the Reformation Occurred in Germany - Ritter, Gerhard (Church history, 1958)
At the end of the Middle Ages, the moral prestige of the old papal church was severely shaken in all the countries of Europe. Open criticism of its moral shortcomings and its organizational defects had been going on for centuries. To the diverse splinter-movements of heretical sects (which were never wholly suppressed) had been recently added the great reform movements of the Wyclifites and the Hussites. But even they had brought about no lasting and widespread upheaval. Ultimately the old hierarchy had always prevailed. Why then did the Germans, a people slow to be aroused, fond of order, and faithful to the church, take it upon themselves to carry out the most prodigious revolution in the church? And why did only their revolt against the papal church have such vast and enduring consequences?